Gain Enhancement of Yagi Slot Antenna using AMC Substrate - Chandran K.P.L.; Samantaray D.; Mohamed A.; Saha C.; Bhattacharyya S. (My University, 2025)
This paper proposes a modified Yagi slot antenna with triple bands and enhanced gain for wearable applications. The proposed design consists of a coplanar fed slot microstrip Yagi antenna backed by an AMC substrate and a ground plane which shows an effective triple operational bandwidth. The AMC has been designed to operate at 7.9 GHz and the performance comparisons have been carried out with and without using AMC substrate. The AMC layer comprises 5×7-unit cell array to form the back reflector for Yagi antenna. The proposed antenna exhibits 4.2%, 12% and 1.6% impedance bandwidths corresponding to 2.84 GHz, 7.64 GHz and 9.66 GHz respectively. The overall gain enhancement of about 8 dBi has been achieved and shows end fire characteristics. The proposed antenna with high gain is a potential candidate for RFID, defense and several medical applications. © 2020 Indian Radio Science Society.